A STUDY ON BRAKING PERFORMANCE OF UTEM ECO-CAR DISC BRAKE SYSTEM - Khalid, Mohamad Kamal; Mansor, Muhd Ridzuan; Mohd Tahir, Musthafah; Hassan, Muhammad Zahir; Tamaldin, Noreffendy (2011)
Braking system is a part of the essential component inside a reliable vehicle. In this project, the braking performance for the UTeM Eco-Car disc brake system which participated in the Perodua Eco-Challenge 2011 competition was analysed using finite element analysis. The brake system characteristics in term of its thermal properties were determined in transient condition. Results from the thermal analysis showed that the maximum temperature generated at the brake disc surface was 119.2oC, which is within the allowable service temperature of the disc material. This shows that the UTeM Eco-Car disc brake system is able to perform safely as per design requirement.